A Systematic Review of the Clinical Use of Gabapentin and Pregabalin in Bipolar Disorder - Qin Xiang Ng; Ming Xuan Han; Seth En Teoh; Clyve Yu Leon Yaow; Yu Liang Lim; Kuan Tsee Chee (MDPI AG, 2021)
Despite its prevalence and disease burden, several chasms still exist with regard to the pharmacotherapy of bipolar disorder (BD). Polypharmacy is commonly encountered as a significant proportion of patients remain symptomatic, and the management of the depressive phase of the illness is a particular challenge. Gabapentin and pregabalin have often been prescribed off-label in spite of a paucity of evidence and clinical practice guidelines to support its use. This systematic review aimed to synthesize the available human clinical trials and inform evidence-based pharmacological approaches to BD management. A total of six randomized, controlled trials (RCTs) and 13 open-label trials involving the use of gabapentin and pregabalin in BD patients were reviewed. Overall, the studies show that gabapentin and its related drug pregabalin do not have significant clinical efficacy as either monotherapy or adjunctive therapy for BD. Gabapentin and pregabalin are probably ineffective for acute mania based on the findings of RCT, with only small open-label trials to support its potential adjunctive role. However, its effects on the long-term outcomes of BD remain to be elucidated. The evidence base was significantly limited by the generally small sample sizes and the trials also had heterogeneous designs and generally high risk of bias.